Increasing beef production - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Researchers at the Zimbabwe Ministry of Agriculture's Henderson Research Station are trying to increase beef production in the communal farming areas. For successful beef production, the farmer must ensure his cows produce a calf every 12 months....